Improvement of entrepreneurship skills in building renovation technique - Harisdani, Devin Defriza; Hadinugroho, Dwi Lindarto; Rambe, Andy Putra (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Increasing the number of routine worship activities and the reduced quality of worship facilities services forced the Al Jihad Mosque, Siti Rejo II Village, Medan Amplas District and surrounding communities to carry out renovation of development in a self-managed / independent manner. In the implementation of the initial stages of the renovation there was a problem of the lack of knowledge and skills of human and community resources regarding building renovation techniques. To be the solution to the problem mentioned above, together with the Universitas Sumatera Utara (USU) TALENTA 2019 Community Service Team, the mosque management as the responsible and stakeholders in improving the quality of community human resources in its organization will carry out activities of understanding building drawings, controlling building costs and simulating stone and wood construction in a micro practice in building renovations. Activities to improve the quality of the community through this knowledge and skills will develop the characteristics of community entrepreneurship in the field of building renovation services or techniques.